Taxing stock transfers in the first golden age of financial capitalism: political salience and the limits on the power of finance. (30th October 2017) - Massoc, Elsa
Abstract: The current debate about taxing financial transactions is often presented as a brand new one. It is not. At the turn of the 19th century, a similar tax was debated in France and the US Financial actors fought the tax mightily. Those actors were very powerful. Yet, they lost. A tax on stock transfers (STT) was established. Why? Through a comparative analysis of France and the State of New York, this article argues that the tax was adopted because politicians interested in capitalizing on public discontent endeavored to publicize and frame the STT in simple and antagonizing terms. Strong but heterogeneous public hostility against finance got focused on the explicitly politicized issue of the tax. Political salience disrupted the logics of 'quiet politics' and momentarily undermined the privileged position of finance. Despite intense lobbying and threats to relocate from financiers, elected officials chose to vote for the STT.